ANALISIS MODEL DAN MEDIA PEMBELAJARAN YANG DIGUNAKAN OLEH GURU PADA MATA PELAJARAN EKONOMI DI SMA SE-KECAMATAN INDERALAYA - Tazkia Ramadhani; Dewi Koryati; Deskoni Deskoni (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2015)
This research wants to describe the learning models and media applied by teachers teaching the Economics subject at SMA in the sub-districts of Indralaya and 4 teachers teaching the Economics subject asked as the samples. The data collection in this study is done by using the technique of documentation, observation, and interviews but the analysis techniques is done descriptively. The results showed that the teachers use the direct instructional model, discussion learning models, and cooperative learning model, while the instructional media used is a visual medium, such as original drawings, concept maps made from cardboard, and use of a whiteboard as a learning medium. The learning plan created and used by teachers has been excellent with an average score of 75%, the ability of teachers in implementing the learning process, the learning evaluation model, and the use of instructional media is categorized into good grade of average score reached 78.2%.